Pemilahan Sampah Organik Dan Non-Organik Terhadap Kebersihan Dan Kesehatan Lingkungan Warga RT 007 Kelurahan Pematang Gubernur Kota Bengkulu - Rahmadania, Della; Ulandia, Emelia Try; Cantika, Yella; Setiawan, Youngky; Risq, Eldy Gunawan; Hanila, Siti; Suwarni, Suwarni; Mujiono, Mujiono (Universitas Dehasen Bengkulu, 2025)
Waste is a serious problem that is often faced in today's population. This KKN activity was carried out at RT 07 RW 04 Keluahan Pematang Governor,. The knowledge of the community in RT 07 about waste and its management is still minimal. Lack of supporting facilities also worsened the condition. Therefore, it is important to foster citizens' concern so that they do not arbitrarily throw away waste and educate how to sort waste. Starting from these problems, this community service activity aims to provide solutions through education on the importance of maintaining cleanliness, choosing and differentiating organic and inorganic waste and utilizing processed waste so that it has economic value. The real form of this activity is in the form of socialization and practicing how to select organic and non-organic waste. The method used in the implementation of this KKN-T activity is education through the stages of socialization, licensing, preparation, implementation and evaluation. As a result of this service activity, community members become concerned about the importance of maintaining cleanliness, an increase in understanding of independent waste sorting and knowledge of its benefits. In addition, the people of RT 07 can also find out the benefits of waste processing in the 3R way, namely: Reduce, Reuse, Recycle.